2014
DOI: 10.1007/s11249-014-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imidazolium Ionic Liquid Additives on Lubrication Performance of Propylene Carbonate under Different Electrical Potentials

Abstract: Three different ionic liquids (ILs), 1-octyl-3-methylimidazolium tetrafluoroborate ([OMIm]BF 4 ), 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIm]PF 6 ) and 1-decyl-3-methylimidazolium hexafluorophosphate ([DMIm]PF 6 ), were used as additives in the base ester propylene carbonate (PC) for the lubrication of AISI 4340 steel surfaces. Ball-on-disk friction tests were done under different electrical potentials to investigate the synergetic effect of IL concentration and electrical potential on lubrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 23 publications
3
38
0
Order By: Relevance
“…The experimental results verify the coincident changes in the friction coefficient and the desorption amount of the SDS film, the mechanism of which is consistent with that found in the aqueous SDS solution. When the SDS surfactant was replaced with ionic liquids (ILs), 1-octyl-3-methylimidazolium tetrafluoroborate ([OMIm]BF 4 ), 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIm]PF 6 ), and 1-decyl-3-methylimidazolium hexafluorophosphate ([DMIm]PF 6 ), a similar effect of the potential on boundary lubrication was found [129], suggesting that the adsorption of ions contributes greatly to boundary lubrication of the IL additives, and that the boundary lubricating ability can be improved to the utmost by applying a proper electrical potential to the steel surface. This mechanism even applies to pure IL as lubricant, with different types of adsorbed ion on the friction pair at different surface potentials [130].…”
Section: Potential Controlled Boundary Lubrication In Non-aqueous Solmentioning
confidence: 93%
See 1 more Smart Citation
“…The experimental results verify the coincident changes in the friction coefficient and the desorption amount of the SDS film, the mechanism of which is consistent with that found in the aqueous SDS solution. When the SDS surfactant was replaced with ionic liquids (ILs), 1-octyl-3-methylimidazolium tetrafluoroborate ([OMIm]BF 4 ), 1-octyl-3-methylimidazolium hexafluorophosphate ([OMIm]PF 6 ), and 1-decyl-3-methylimidazolium hexafluorophosphate ([DMIm]PF 6 ), a similar effect of the potential on boundary lubrication was found [129], suggesting that the adsorption of ions contributes greatly to boundary lubrication of the IL additives, and that the boundary lubricating ability can be improved to the utmost by applying a proper electrical potential to the steel surface. This mechanism even applies to pure IL as lubricant, with different types of adsorbed ion on the friction pair at different surface potentials [130].…”
Section: Potential Controlled Boundary Lubrication In Non-aqueous Solmentioning
confidence: 93%
“…Yang et al [129] choose the SDS surfactant in a pure propylene carbonate based fluid as a model lubricant to investigate the effect of potential on friction. Propylene carbonate is a polar aprotic solvent and is frequently used as a high permittivity component of electrolytes in lithium batteries.…”
Section: Potential Controlled Boundary Lubrication In Non-aqueous Solmentioning
confidence: 99%
“…Since some ionic liquids are soluble in base oils they may also act as supporting electrolytes in lubricants. Yang, Meng, and Tian have studied the effect of electrode potentials on Pt with solutions of imidazoline-based ionic liquid in propylene carbonate using cyclic voltammetry [98,99]. They found that the solutions gave low friction at negative potentials and high friction at positive potentials that they ascribed to the adsorption of the cation and anion species, respectively.…”
Section: Recent Research On Triboelectrochemistrymentioning
confidence: 99%
“…In addition, it is necessary to be aware that the sliding material does not cause electric corrosion. Yang et al used steel as sliding materials [28]. It is possible that the electric corrosion of steel will become.…”
Section: Introductionmentioning
confidence: 99%